Capsular inflammation after immediate breast reconstruction – Gene expression patterns and inflammatory cell infiltration in irradiated and non-irradiated breasts. (January 2023) - Frisell, A.; Bergman, O.; Khan, A.; Gisterå, A.; Fisher, R.M.; Lagergren, J.; de Boniface, J.; Halle, M.
Summary: Background: Capsular contracture following post-mastectomy radiotherapy (PMRT) is commonly seen in patients undergoing implant-based immediate breast reconstruction (IBR). Further understanding of the underlying biology is needed for the development of preventive or therapeutic strategies. Therefore, we conducted a comparative study of gene expression patterns in capsular tissue from breast cancer patients who had received versus those who had not received PMRT after implant-based IBR. Methods: Biopsies from irradiated and healthy non-irradiated capsular tissue were harvested during implant exchange following IBR. Biopsies from irradiated ( n  = 13) and non-irradiated ( n  = 12) capsules were compared using Affymetrix microarrays to identify the most differentially regulated genes. Further analysis using immunohistochemistry was performed in a subset of materials to compare the presence of T cells, B cells, and macrophages. Results: Enrichment testing using Gene Ontology (GO) analysis revealed that the 227 most differentially expressed genes were mainly involved in an inflammatory response. Twenty-one GO biological processes were identified [ p < 0.05, false discovery rate (FDR) < 5%], several with B-cell-associated inflammation. Cell-type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT) analysis identified macrophages as the most common inflammatory cell type in both groups, further supported by immunostaining of CD68. Radiation remarkably increased B-cell infiltration in the capsular region of biopsies, as quantified by immunostaining of CD20 ( p  = 0.016). Conclusions: Transcript analysis and immunohistochemistry revealed inflammatory responses in capsular biopsies regardless of radiotherapy. However, the radiation response specifically involved B-cell-associated inflammatory responses.